EFEKTIVITAS PERKOTAAN GEMOLONG SEBAGAI PUSAT PELAYANAN PERMUKIMAN DI KABUPATEN SRAGEN - Sari, Sri Murdiati Rin Permata; Hardiana, Ana; Putri, Rufia Andisetyana (Regional Development Information Center, Universitas Sebelas Maret, 2016)
The existence of dependency between residential service center with service area then resulted in the slice of service range from some service center adjacent. Urban Gemolong as a residential service center with six sub-districts as its service area (Gemolong, Miri, Sumberlawang, Plupuh, Kalijambe, Tanon), does not yet have a complete settlement service as well as the location of the big city (Solo, Porwodari, Boyolali) There is a tendency for the service area to not meet the needs of its services in urban Gemolong. The problem formulation in this research is how effectiveness of urban Gemolong as settlement service center in Sragen regency? The purpose of the study is the effectiveness of urban Gemolong as a settlement service center in Sragen regency. Research method in this research is deductive, with kind of quantitative research. Analytical techniques in this study is scoring analysis for suitability on each variable, and for assessment of its effectiveness by percentage approach. The conclusion obtained in this study is the effectiveness of urban Gemolong as a settlement service center in Sragen regency in the form of effective approach. Approaching effectively means that urban Gemolong as a settlement service center is in a near-successful position (approaching effectively) in fulfilling its role as a settlement service center in terms of goals, efficiency or affordability. Called approaching to succeed because of the three vaiabel approaches, there is an approach that states that viewed from the side of goals, urban Gemolong has been appropriate (effective from the side of the goal). From the approach of affordability and efficiency that is how the community to reach the service and how the availability of the number of facilities when compared with the population is still not appropriate (not yet effective). Urban Gemolong needs to improve the existing resettlement service especially from efficiency and affordability approach in order to fulfill its function and role as residential service center, in several ways that is the addition of the number of settlement service facilities, shifting and arranging the layout of the facilities so that the needs of facilities availability and affordability of the facilities are met